Corruption in the health care sector: A barrier to access of orthopaedic care and medical devices in Uganda - Bouchard Maryse; Kohler Jillian C; Orbinski James; Howard Andrew (BMC, 2012)
Abstract Background Globally, injuries cause approximately as many deaths per year as HIV/AIDS, tuberculosis and malaria combined, and 90% of injury deaths occur in low- and middle- income countries. Given not all injuries kill, the disability burden, particularly from orthopaedic injuries, is much higher but is poorly measured at present. The orthopaedic services and orthopaedic medical devices needed to manage the injury burden are frequently unavailable in these countries. Corruption is known to be a major barrier to access of health care, but its effects on access to orthopaedic services is still unknown. Methods A qualitative case study of 45 open-ended interviews was conducted to investigate the access to orthopaedic health services and orthopaedic medical devices in Uganda. Participants included orthopaedic surgeons, related healthcare professionals, industry and government representatives, and patients. Participants' experiences in accessing orthopaedic medical devices were explored. Thematic analysis was used to analyze and code the transcripts. Results Analysis of the interview data identified poor leadership in government and corruption as major barriers to access of orthopaedic care and orthopaedic medical devices. Corruption was perceived to occur at the worker, hospital and government levels in the forms of misappropriation of funds, theft of equipment, resale of drugs and medical devices, fraud and absenteeism. Other barriers elicited included insufficient health infrastructure and human resources, and high costs of orthopaedic equipment and poverty. Conclusions This study identified perceived corruption as a significant barrier to access of orthopaedic care and orthopaedic medical devices in Uganda. As the burden of injury continues to grow, the need to combat corruption and ensure access to orthopaedic services is imperative. Anti-corruption strategies such as transparency and accountability measures, codes of conduct, whistleblower protection, and higher wages and benefits for workers could be important and initial steps in improving access orthopaedic care and OMDs, and managing the global injury burden.